Pengaruh Kualitas Produk Dan Content Marketing Terhadap Keputusan Pembelian Produk Wardah Pada Gen-Z Di Kota Palembang - Samosir, Lidia Karunia May; Helmi, Sulaiman; Roni, Mukran; septayuda, Irwan (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
This study aims to analyze the influence of product quality and content marketing on the purchasing decisions of Wardah products among Generation Z consumers in Palembang City. The phenomenon observed is that Gen Z tends to make purchasing decisions based on social media content rather than product quality, as they are a generation highly active on social media. Therefore, digital marketing strategies through content marketing are highly relevant. The research employed a quantitative approach using the SEM-PLS technique on 104 Gen Z respondents who had previously purchased Wardah products and engaged with its social media content. The findings reveal that both product quality and content marketing significantly influence purchasing decisions, with product quality exerting a more dominant effect. This study provides practical contributions for companies in developing effective and relevant digital marketing strategies, as well as serving as an academic reference in the study of digital consumer behavior.